Effect of avermectin-containing polyfunctional biostimulants on wheat tole rance to salt stress - Pushkarova, N.O.; Plohovska, S.H.; Horiunova, I.I.; Buziashvili, A.Yu.; Melnychyk, O.V.; Pastuhova, N.L.; Chugunkova , T.V.; Yemets, A.I.; Blume , Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2022)
Salt stress negatively affects plants growth and development especially on early stages of ontogenesis. The polyfunctional avermectin-containing biostimulants of bacterial origin, in particular Avercom and Avercom Nova, application for overcoming this stress negative effect is highly promising. The aim of this work is to study these biostimulants effect on wheat (Elegia Myronivska, Oksamyt Myronivskiy and Zlata varieties) tolerance to salt stress. It was shown that seeds pre-sowing treatment with Avercom had protective effect on plants growth and development under salt stress on early stages of ontogenesis (up to 14 days) when grown in the presence of 100 mM of NaCl. However, Avercom Nova was shown to be more effective in case of prolong exposure of wheat to salt stress.